2006
DOI: 10.1071/wf05066
|View full text |Cite
|
Sign up to set email alerts
|

Predicting and mitigating weed invasions to restore natural post-fire succession in Mesa Verde National Park, Colorado, USA

Abstract: Six large wildfires have burned in Mesa Verde National Park during the last 15 years, and extensive portions of burns were invaded by non-native plant species. The most threatening weed species include Carduus nutans, Cirsium arvense, and Bromus tectorum, and if untreated, they persist at least 13 years. We investigated patterns of weed distribution to identify plant communities most vulnerable to post-fire weed invasion and created a spatially explicit model to predict the most vulnerable sites. At the scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 32 publications
1
52
2
Order By: Relevance
“…This lack of post-fire invasion contrasts with other recent studies where exotic species had high abundance following wildfire (e.g., Crawford et al, 2001;Griffis et al, 2001;Floyd et al, 2006). Had the treatments increased plant cover significantly, the lack of response in this study would have been encouraging, suggesting that exotic plant introductions through seeding were minimal and that fertilization did not significantly facilitate the spread of existing exotic plant populations.…”
Section: Treatment Effects On Exotic Speciescontrasting
confidence: 82%
See 1 more Smart Citation
“…This lack of post-fire invasion contrasts with other recent studies where exotic species had high abundance following wildfire (e.g., Crawford et al, 2001;Griffis et al, 2001;Floyd et al, 2006). Had the treatments increased plant cover significantly, the lack of response in this study would have been encouraging, suggesting that exotic plant introductions through seeding were minimal and that fertilization did not significantly facilitate the spread of existing exotic plant populations.…”
Section: Treatment Effects On Exotic Speciescontrasting
confidence: 82%
“…Aerial seeding is used to rapidly restore plant cover where severe wildfire has killed vegetation and consumed organic soil cover (Robichaud et al, 2000) and, in some cases, to inhibit the invasion and spread of exotic plant species (Beyers, 2004;Floyd et al, 2006). Seeding is the most widely used post-fire stabilization treatment, but its effectiveness for increasing plant cover has been variable (Robichaud et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It was gratifying to observe that cover of exotic species was low in the first 3 years after the Rodeo-Chediski fire, despite our expectations to the contrary. While our study was short-term in scope during a drought period, other studies have seen an explosion of exotic species populations within 2 to 3 years following fire Floyd et al, 2006;Wienk et al, 2004). The White Mountain Apache tribal land has been managed for logging, grazing, and hunting, unlike preserves that had similar low post-fire responses by exotics.…”
Section: Discussionmentioning
confidence: 97%
“…Most of the remaining exotic species include firefollowers, or other species such as common mullein, which is listed as noxious in Colorado, but tends to be ephemeral a few years after disturbances (Sieg et al, 2003). The possibility of a sudden and rapid proliferation of existing exotic species such as Floyd et al (2006) observed can only be addressed by continuing to monitor these sites in the future.…”
Section: Discussionmentioning
confidence: 98%
“…Cheatgrass was the dominant non-native grass on our wildfire sites, constituting nearly 8% of the total standing crop. Whether it eventually disappears, as was observed following a wildfire in California (Countryman and Cornelius, 1957), or dramatically expands, as noted by Floyd et al (2006) following wildfires in Mesa Verde National Park, remains to be seen. Given the risk of accidentally introducing species such as cheatgrass, the need for seeding projects should be carefully assessed.…”
Section: Influence Of Disturbance On Plant Community Compositionmentioning
confidence: 88%